Association of Evening Eating with Sleep Quality and Insomnia among Adults in a Brazilian National Survey - Maria Eduarda Bezerra Nunes; Caio Henrique Barros dos Santos; Márcia de Oliveira Lima; Anny Kariny Pereira Pedrosa; Risia Cristina Egito de Menezes; Giovana Longo-Silva (Sleep Science)
Objective To examine the association of evening eating clock time, its elapsed time to the midpoint of sleep (TEM), consumption of caffeine and sugary foods, and dinner meal size with sleep quality indicators and insomnia.